Influence of Gender on Learners’ Retentive Performance in Literary Appreciation Using Reciprocal Peer Learning Approach - Assimonye, Augusta Chiedu (Teaching, Learning, and Development, 2024)
The persistent challenge of poor retention and comprehension among students in literary appreciation has continued to attract the attention of educators and researchers. Many learners struggle to sustain long-term understanding of literary concepts due to the teacher-centere